The Effect Of The Discovery Learning Model On Students' Understanding Of Mathematical Concepts In Grade VIII - Rumapea, Mutiara Sani; Sinaga, Christa Voni Roulina; Simanungkalit, Rick Hunter (Jurnal Pendidikan, Sains Sosial, dan Agama, 2020)
This study aims to determine the effect of the Discovery Learning model on students’ mathematical conceptual understanding in grade VIII of SMP Negeri 4 Pematangsiantar. The sample of this study was class VIII-10 consisting of 30 students. The research instruments were a questionnaire and a test. The questionnaire was used to identify the implementation of the Discovery Learning model, while the test was used to measure students’ conceptual understanding of linear equations. The instruments consisted of 20 questionnaire items and 4 test items, which had been validated and declared reliable. The research design employed a one-shot case study. Data analysis included prerequisite tests (normality and linearity) and simple linear regression analysis. The results of the study showed the regression equation Y=6.571+0.411XY = 6.571 + 0.411X. The significance test revealed that tcount>ttablet_{count} > t_{table} (8.194 > 2.048) and sig. value < 0.05 (0.000 < 0.05), indicating a significant effect of the Discovery Learning model on students’ mathematical conceptual understanding. The contribution of variable X (Discovery Learning model) to variable Y (mathematical conceptual understanding) was 70.6%..